Distributed Leadership: A Potential Agency for Traversing Power Relations as Impediments to Curriculum Transformation and Implementation of Environmental Education - Shabalala, Nonkanyiso Pamella; Hebe, Headman; Mnguni, Lindelani (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2023)
Decades after the 1972 United Nations Conference on the Human Environment held in Stockholm declared environmental education (EE) an essential tool to mitigate environmental challenges, the implementation of EE still faces many obstacles. Accordingly, innovative, and solution-oriented approaches remain vital to enable environment-driven pedagogy in formal and non-formal education settings. This paper, which is located within the context of a case study that was conducted with the aim to investigate the application of distributed leadership in the teaching of EE in South Africa, reports on hierarchical power relations as impediments to curriculum transformation and implementation and, by extension, a hindrance to the infusion of EE in pedagogy. The results of this study suggest that hierarchical power relations in the schooling system hamper the involvement and participation of various stakeholders in key decision-making responsibilities, particularly, curriculum management. Accordingly, processes such as curriculum modification which are essential to enable the implementation of EE are impeded. The researchers of the current study argue that, based on its marked successes in various spaces, especially in the realm of education; distributed leadership could be one of the viable agencies to enable EE implementation.